Portrait of Digital Library Islamic Collection: Study of PTKIN Digital Library Management System in North Sumatera - Muhammad Dalimunte; Toguan Rambe; Kasron Nasution (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2022)
This research aims to reveal at the management of human resources and the management of digital systems in the libraries of state Islamic universities, specifically in the North Sumatra region, namely UIN North Sumatra Medan, IAIN Padangsidimpuan and STAIN Mandailing Natal. This study used a qualitative approach with data sources are the head of the library, librarians and users, both lecturers and students. This research data collection technique used observation sheets, interviews and focus group discussions so that the resulting data is more comprehensive. The data that has been collected is analyzed with interpretation. The results of the study indicate that there is an imbalance between users and human resources, this is the cause of the service in the library is not good. Increasing the quality of human resources in the PTKIN library in the North Sumatra region is very urgent to be carried out to optimize performance and become a driver of other resources more optimally. This optimization is also to support the competitiveness of libraries in this massive digitalization era, so scientific knowledge development is progressively advanced in Islamic universities in North Sumatra. This optimization is also to support the competitiveness of libraries in this massive digitalization era, so that the development of scientific knowledge is progressively advanced in Islamic universities in North Sumatra.